Clinical Characteristics and Follow-Up of Seizures in Children With Anti-NMDAR Encephalitis - Zhang, Jianzhao; Sun, Jing; Zheng, Ping; Feng, Shuo; Yi, Xiaoli; Ren, Haitao; Chen, Qian (Frontiers in Neurology, 2022)
Objective: To analyze the seizure characteristics of children with anti-NMDAR encephalitis. Methods: This was a retrospective analysis of 50 children with anti-NMDAR encephalitis between July 1, 2013, and July 1, 2019. Results: Fifty children with anti-NMDAR encephalitis were included in this study, of which 34 (68.0%) had seizures. During at least 1 year of follow-up, except for 3 patients with anti-NMDAR encephalitis secondary to herpes simplex virus encephalitis who had persistent seizures, the average duration of seizures in the remaining children was 14.6 days (range 1 to 47 days). Compared to patients without seizures, those with seizures were more likely to experience consciousness disturbances (p=0.008) and epileptic form discharge on electroencephalograms (p=0.002). The Glasgow scores (p=0.014), and Rankin scale scores (p=0.019) were also different. The cranial MRI findings of children were reviewed, and clinical characteristics were compared between children without cranial lesions and those with lesions in the limbic system and neocortex. Compared to children in the non-lesion group, children with lesions in the limbic system and neocortex had a higher incidence of status epilepticus. Further, children in the limbic system and neocortical lesions groups were more likely to be taking anti-seizure medications (ASMs) and receive second-line drugs. Conclusion: Long-term oral ASMs are not recommended for most children with anti-NMDAR encephalitis. Children with involvement of the limbic system and neocortex are prone to status epilepticus, and sequelae of epilepsy may remain when the neocortex is involved.